2016
DOI: 10.1152/ajpcell.00091.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent and independent roles of SUMO in proteostasis

Abstract: Cellular proteomes are continuously undergoing alterations as a result of new production of proteins, protein folding, and degradation of proteins. The proper equilibrium of these processes is known as proteostasis, implying that proteomes are in homeostasis. Stress conditions can affect proteostasis due to the accumulation of misfolded proteins as a result of overloading the degradation machinery. Proteostasis is affected in neurodegenerative diseases like Alzheimer's disease, Parkinson's disease, and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 150 publications
4
81
0
Order By: Relevance
“…The ubiquitin conjugation pathway plays a key role in degrading unneeded cellular proteins, and SUMOylation is a major component of the system that controls the quality of newly synthesized proteins 10, 11, 12. UPR is a highly conserved pathway activated in stress conditions that impair proteostasis and result in accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) 9.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin conjugation pathway plays a key role in degrading unneeded cellular proteins, and SUMOylation is a major component of the system that controls the quality of newly synthesized proteins 10, 11, 12. UPR is a highly conserved pathway activated in stress conditions that impair proteostasis and result in accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) 9.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, we did not detect any significant link between global SUMO1 levels and AD‐like pathology. This finding argues against an involvement of altered SUMO1 conjugation in the pathogenesis of AD, at least as it is apparent in the 5XFAD model, but does not exclude a link to SUMO2/3 conjugation in this model, as SUMO2/3‐conjugation is prone to react more robustly to stress (Bernstock et al., 2018; Liebelt & Vertegaal, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…As proof of principle, we found that the SUMO1 candidates identified by anti‐HA‐based affinity purification followed by mass spectrometric protein quantification were also reported in previous proteomic screens (Table S1, KI‐enriched Sheet), indicating that a large portion of the SUMO1 proteome remains stable, irrespective of the physiological context (Becker et al., 2013; Tirard et al., 2012). Many of the identified candidates are transcriptional regulators (Bcl11a/Ctip1, Bcl11b/Ctip2, Wiz, SmchD1, Trim28), indicating that the main function of SUMO1 conjugation is to guard nuclear functions, as may be particularly the case during age‐related proteostasis stress (Gartner & Muller, 2014; Hendriks & Vertegaal, 2016; Liebelt & Vertegaal, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations